A new species of Cyrtodactylus (Squamata: Gekkonidae) from central New Guinea - Oliver, Paul M.; Karkkainen, Denise Taimi; Rösler, Herbert; Richards, Stephen J. (Zootaxa, 2019)
We describe a new species of bent-toed gecko in the genus Cyrtodactylus from hill forest in Southern Highlands Province, Papua New Guinea. Cyrtodactylus manos sp. nov. can be distinguished from all congeners in New Guinea by its small size in combination with aspects of colouration and body and tail scalation. The new species adds to the growing number of vertebrate species known only from karstic mountains along the southern edge of New Guinea’s Central Cordillera, suggesting that this region holds previously overlooked endemic karst-associated biota.